2019
DOI: 10.1200/jco.2019.37.15_suppl.5004
|View full text |Cite
|
Sign up to set email alerts
|

TAXOMET: A French prospective multicenter randomized controlled phase II study comparing docetaxel plus metformin versus docetaxel plus placebo in mCRPC.

Abstract: 5004 Background: Docetaxel (DOCE) is a standard of care in metastatic castration-resistant prostate cancer (mCRPC). Several retrospective cohort studies suggest a decrease in PC incidence and mortality with metformin (MET). MET has also demonstrated anti-tumor activity in PC preclinical models, with increase apoptosis when added to DOCE. The addition of MET could enhance DOCE efficacy in mCRPC patients (pts). Methods: TAXOMET is a phase II prospective multicentric randomized controlled trial. Non-diabetic mCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To date, there has been only one reported randomised trial examining the use of metformin in mCRPC, the phase II TAXOMET study in which 99 patients with mCRPC were randomised to treatment with docetaxel plus metformin versus docetaxel alone in order to increase the estimated PSA-RR from 45 to 60%. No differences in the primary end-point of PSA response rate was seen [ 15 ] and the median OS was 24.2 months (95% CI 17.2–33.7) in the combination arm versus 19.7 months (95% CI 14.8–36.8) with docetaxel alone, which did not meet statistical significance [ 15 ]. A small phase II pilot study of 25 men with mCRPC demonstrated that the addition of metformin after PSA progression on abiraterone did not affect further progression and had no meaningful clinical benefit [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been only one reported randomised trial examining the use of metformin in mCRPC, the phase II TAXOMET study in which 99 patients with mCRPC were randomised to treatment with docetaxel plus metformin versus docetaxel alone in order to increase the estimated PSA-RR from 45 to 60%. No differences in the primary end-point of PSA response rate was seen [ 15 ] and the median OS was 24.2 months (95% CI 17.2–33.7) in the combination arm versus 19.7 months (95% CI 14.8–36.8) with docetaxel alone, which did not meet statistical significance [ 15 ]. A small phase II pilot study of 25 men with mCRPC demonstrated that the addition of metformin after PSA progression on abiraterone did not affect further progression and had no meaningful clinical benefit [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the SAKK 08/09 study using metformin as monotherapy, only 2/44 patients had a PSA 50 response. In the recently presented TAXOMET study, 99 patients with mCRPC who were non-diabetic were randomised between standard docetaxel and prednisone and the addition of metformin (850 mg twice daily); no statistical differences were detected in this small study with limited duration of metformin in any clinically meaningful end-point [ 20 ]. One-third of the patients remained progression free at 12 weeks posttreatment with metformin and the PSA doubling time was prolonged in half of the patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%